Rua da Bahia: patrimônio cultural, arquitetura e memória - Luciana de Carvalho Teixeira (2015)
The purpose of this work is the study of changes and maintenance that take place in urban space built in the city of Belo Horizonte in the light of municipal policy of cultural heritage protection. The wear of forms which fall within the urban space, caused by the passing of time, makes them often unrecognizable or unrecoverable. In Belo Horizonte, this wear is marked by successive demolitions and (re) buildings. Starting from the assumption that the architecture and the urban landscape are supports for the collective memory, and taking as reference the central area of Belo Horizonte, it was made an analysis of the urban landscape of the present and the past, its transformations and conditions that enabled the successive changes. Thus, it is taken as focus the Conjunto Urbano Rua da Bahia e Adjacências, chosen from among the other Urban Sets protected because Rua da Bahia has a significant historical-architectural and cultural heritage, and is also the place where occurred the first protection of intangible heritage at the municipal level: the tipping of Cantina do Lucas, located in the Edifício Arcângelo Maletta. Through this research is expected to contribute to the preservation of the built in support for collective memory and quality of life generator in the review and implementation of tools and protective methods and studies on the topic of cultural heritage.